Rin, norA, ogc and hp mutants in tomatos with different genetic backgrounds - Faria, Marcos Ventura; Maluf, Wilson Roberto; Resende, Juliano Tadeu Vilela de; Andrade-Júnior, Valter Carvalho; Nascimento, Ildon Rodrigues do; Benites, Flávio Rodrigo Gandolfi; Menezes, Cícero Beserra de; Azevedo, Sebastião Márcio (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to assess the viability of single and simultaneous use of rin, norA, ogc and hp as heterozygotes in tomato genotypes in order to improve post-harvest fruit quality. Eighteen genotypes differing in combinations among these loci in two backgrounds (Floradade and experimental background) were evaluated. Contrasts were used to quantify the effects of single and simultaneous application of mutant loci, in two different backgrounds, on the total and early fruit yield, fruit mean mass, fruit firmness, development of external fruit color, lycopene and beta-carotene fruit contents. The norA and the rin alleles, used as heterozygotes in the FloraDade background, delayed the fruit softening and reduced lycopene and beta-carotene contents of mature fruit. All heterozygous combinations between rin and the mutants norA, ogc and hp increased fruit firmness. The effect of the rin+/rin nor+/norA genotypes on fruit firmness was roughly the sum of the individual effects of each locus. The rin allele was more efficient than norA to keep fruit firmness. The ogc+/ogc and hp+/hp genotypes, singly or in combination, improved colour of rin fruits. The combination rin+/rin and nor+/norA can be used in breeding for long shelf life tomatoes; however, genotypic backgrounds where fruit colour is less adversely affected should be sought or, alternatively, the colour mutant heterozygotes ogc+/ogc and hp+/hp should be used.